Comparison of reliability of thermoelectric generator modules with different schemes for connecting thermoelements - Petrо Gorskyi (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The study compares reliability indicators of thermoelectric generator modules using the nonmonotonic-diffusion law of failure time distribution. The authors use the law to propose for the first time an analytical expression of the failure time distribution of an individual thermoelement, which fundamentally differs from the traditional simple exponential law with a constant failure intensity. The law is used to calculate the mean time between failures (MTBF), the 95% resource and equivalent failure rate of thermoelectric generator modules with series-parallel and parallel-series connection of thermocouples. Considered are the variants of schemes with different number of elements in rows and different number of rows for serial-parallel circuit and with different number of sequential groups and elements in a group for parallel-serial circuit. Coefficients of increase of the average failure time, 95% resource and coefficients of decrease of the equivalent failure intensity for a purely series connection of thermocouples are determined for the considered thermocouple schemes. It is established that these indicators can be improved by more than three orders of magnitude.